Antimicrobial activity of antibiotics on biofilm formed by Staphylococcus aureus and Pseudomonas aeruginosa in an open microfluidic model mimicking the diabetic foot environment. (28th December 2022) - Pouget, Cassandra; Pantel, Alix; Dunyach-Remy, Catherine; Magnan, Chloé; Sotto, Albert; Lavigne, Jean-Philippe
Abstract: Background: Diabetic foot infections (DFIs) represent a public health problem because of their frequency and the severity of their consequences, i.e. amputation and mortality. Polymicrobial biofilms on the skin surface of these ulcers complicate wound healing. Few in vitro models exist to study the antibiotics activity in this context. Objectives: This study evaluated the in vitro activity of antibiotics against the two main bacteria isolated in DFI, Staphylococcus aureus and Pseudomonas aeruginosa, using a dynamic system (BioFlux™ 200) and a chronic wound-like medium (CWM) that mimic the foot ulcer environment. Methods: Reference strains and two pairs of clinical S. aureus and P. aeruginosa isolated together from a DFI were cultivated in brain heart infusion and CWM media during 72 h at 37°C, alone and combined in the BioFlux™ 200 system. Antibiotic activity was evaluated after a mechanical debridement. The activities were measured by the reduction of biofilm percentage of bacteria in the microfluidic system using microscopy. Results: Daptomycin for S. aureus and ceftazidime for P. aeruginosa showed excellent activity to reduce biofilm biomass, whereas linezolid action was more mitigated and dalbavancin was ineffective. Ceftazidime + daptomycin presented the most potent in vitro activity on a mixed biofilm. Conclusions: The combination of CWM and the BioFlux™ microfluidic system represents a valuable tool to screen the potential antimicrobial activity of antibiotics under conditions mimicking those encountered in DFI. It could help clinicians in their management of chronic wounds.